Preoperative ultrasound for the diagnosis of thyroglossal duct cysts: A validation study. (July 2019) - Devine, Conor M.; Park, Ellen; Vachhani, Neil; Butler, Robert; Krakovitz, Paul
Abstract: Objectives: To evaluate the use of ultrasound to distinguish between thyroglossal duct cysts (TGDC) and dermoid cysts (DC) for surgical planning. To validate the SIST (septae + irregular wall + solid components = TGDC) scoring system proposed by Oyewumi et al. [1]. Methods: This was a retrospective chart review of pediatric patients with midline neck masses who presented between the years of 2005 and 2014 and underwent preoperative ultrasound and surgical resection. Two pediatric radiologists blinded to diagnosis reviewed each US for 14 separate characteristics. According to the SIST scoring system, one point was given for each of the following: internal septae, irregular walls, and solid components. Results: 45 patients met inclusion criteria. Final pathologic diagnosis showed 29 patients had TGDC, 16 had DC. The majority of patients with both TGDC and DC earned SIST scores of 0. Conclusion: While ultrasound remains a useful part of the work-up of lesions of the head and neck in children, this small retrospective study was not able to validate the previously proposed SIST scoring system None of the parameters discussed in the original paper was found to be a statistically significant determinant of TGDC.